Exposition of Body Aesthetics: Reading Koirala’s Sumnima and Parijat’s Shirisko Phool - Gautam, Mani Bhadra (Literary Studies, 2023)
Sumnima and Shirisko Phool deal with the subject matter of body aesthetics. Koirala’s Sumnima exposes vivacious Sumnima body with ‘strong sense of heroism’ that she straightens in front of dry body, idealistic notion of Somdatta and Parijat’s Shirisko Phool reveals the causes and consequences of Suyogbir’s kissing that kills Bari. Suyogbir fails to preserve his military ethics and social prestige while he is mad in Bari’s bodily beauty and behaviors. Somdatta’s spiritual salvation of Khas-Aryan stocks in the name of achieving divinity by the power of penance makes victim to a Kirat girl, Sumnima, for a long and she ultimately marries with a village boy from Kirat community and gives birth to a daughter. Comparative study compares two or more than two people, places, things, arts, culture/religion and literature and this is a comparative study on Koirala and Parijat characters’ body aesthetics in Sumnima and Blue Mimosa. This comparative study’s objective is to bring prolong history of body aesthetics of Suryadatta, Somdatta, Bhilla, Puloma and Sumnima in Sumnima and Suyogbir, Shivaraj, Mujura, Sanu and Sakambari in Shirisko Phool for which I take theoretical support from Susan Bassnett, Charles Bernheimer, Jonathan Culler, David Ferry, Guillen Clandio, Jost Francis, Remak H.H.etc.’s ideas. Koirala and Parijat characters expose body aesthetics, experience ups and down of social practices and continue and/or break throw them from multiple aspects. The narratives in Sumnima and Blue Mimosa also focus on divine power for spiritual living, too but this study highlights an exposition of body aesthetics.